A Carnuntumban állomásozó katonák vallása feliratos emlékeik tükrében - Papp, László (Hallgatói Műhelytanulmányok, 2022)
Papp, László: Religion of soldiers stationed in Carnuntum in the light of their epigraphical memories In my study I examine the roman soldiers’ religion stationing at Carnuntum based on their inscriptions. I am looking for the connection between the soldiers’ profession, origin, where they were formerly stationed and the cults. Soldiers stationing at Carnuntum just like the ones deployed in other parts of the empire often presented their loyalty to the emperor through inscriptions. Mithras and Iuppiter Dolichenus were usually the favourites of many soldiers, but not for the ones’ who were stationing at Carnuntum, according to the inscriptions they preferred Silvanus and Nemesis instead. Although many images on gravestones are referring to after-life, it is hard to decide whether these images carried symbolic meanings or they were only used as ornamentation.